High permittivity and low loss microwave dielectrics suitable for 5G resonators and low temperature co-fired ceramic architecture. Issue 38 (26th September 2017) - Zhou, Di; Pang, Li-Xia; Wang, Da-Wei; Li, Chun; Jin, Biao-Bing; Reaney, Ian M.
Abstract : Bi2 (Li0.5 Ta1.5 )O7 ceramics possess a ε r of 65.1, a Q f of 15 500 GHz and a TCF of −17.5 ppm °C −1 . The sintering temperature was lowered to 920 °C by the addition of 2 mol% Bi2 O3, which makes them potential candidates for dielectric resonators and LTCC applications. Abstract : Bi2 (Li0.5 Ta1.5 )O7 + x Bi2 O3 ( x = 0, 0.01 and 0.02) ceramics were prepared using a solid state reaction method. All compositions were crystallized in a single Bi2 (Li0.5 Ta1.5 )O7 phase without secondary peaks in X-ray diffraction patterns. Bi2 (Li0.5 Ta1.5 )O7 ceramics were densified at 1025 °C with a permittivity ( ε r ) of ∼ 65.1, Q f ∼ 15 500 GHz ( Q ∼ microwave quality factor; f ∼ resonant frequency; 16 780 GHz when annealed in O2 ) and the temperature coefficient of resonant frequency (TCF) was ∼ −17.5 ppm °C −1 . The sintering temperature was lowered to ∼920 °C by the addition of 2 mol% excess Bi2 O3 ( ε r ∼ 64.1, a Q f ∼ 11 200 GHz/11 650 GHz when annealed in O2 and at a TCF of ∼ −19 ppm °C −1 ) with compositions chemically compatible with Ag electrodes. Bi2 (Li0.5 Ta1.5 )O7 + x Bi2 O3 are ideal for application as dielectric resonators in 5G mobile base station technology for which ceramics with 60 < ε r < 70, high Q f and close to zero TCF are commercially unavailable. They may additionally prove to be useful as high ε r and high Q f materials in low temperature co-fired ceramic (LTCC) technology.